[DMEDA]PbCl4: a one-dimensional organic lead halide perovskite with efficient yellow emission. Issue 8 (11th February 2020) - Sun, Chen; Yue, Yun-Di; Zhang, Wei-Feng; Sun, Xing-Yu; Du, Yan; Pan, Hong-Mei; Ma, Yue-Yu; He, Yuan-Chun; Li, Meng-Ting; Jing, Zhi-Hong
Abstract : By using a simple room temperature solution reaction, we prepared a new type of one-dimensional (1D) hybrid lead halide [DMEDA]PbCl4 . The compound gives a bright yellow emission with efficient photoluminescence quantum efficiency (PLQE) and optical stability. Abstract : In recent years, low-dimensional organic–inorganic hybrid lead halide perovskites have been explored as photoluminescent (PL) materials with high photoluminescence quantum efficiencies and tunable band structures arising from the structural regulating functions of organic cations. Herein, by using a simple solution reaction, we prepared one new type of one-dimensional (1D) hybrid lead halide, namely [DMEDA]PbCl4 (DMEDA = N, N ′-dimethylethylenediamine). The compound contains 1D edge sharing octahedral lead chloride [PbCl4 ] 2− anionic chains, which are surrounded and separated by organic cations of [DMEDA] 2+ . This 1D structure enables the formation of self-trapped excited states that give bright yellow emission with a photoluminescence quantum efficiency (PLQE) of approximately 4.81%. A white light emitting device can also be easily fabricated by coating a sample of [DMEDA]PbCl4 on a blue light chip. Its PL stability and nature are also investigated by using various experiments. This work provides a new type of structural model to probe the PL properties and understand the structure–property relationship of low-dimensional lead halide perovskites.